Economic Loss of Leptospirosis: Is It Still Appropriate to be Tropical Neglected Zoonosis Disease? - Nugraheni, Wahyu Pudji; Lestyoningrum, Sinta Dewi; Ristiyanto, Ristiyanto; Putro, Wahyu Gito; Pawitaningtyas, Indah; Nuraini, Syarifah; Putri, Linta Meyla; Faisal, Debri Rizki; Noveyani, Adhista Eka; Mikrajab, Muhammad Agus (Kesmas, 2024)
Leptospirosis is a tropical endemic disease that can reduce the productivity of sufferers. However, research on economic and productivity losses due to leptospirosis is rare. This study aimed to determine economic and productivity losses due to leptospirosis in the Banyumas District, Indonesia, as an endemic area. This study used a cross-sectional design and quantitative methods conducted in October 2022. Secondary data of medical records and billing information from 73 inpatients receiving treatment at a Public Hospital in the Banyumas District from February 2021 to September 2022 obtained from the hospital’s archives were used. This study examined the actual costs (direct and indirect costs) of treatment, average length of stay, and patient characteristics. Statistical tools were carried out to check the results. The results showed that over half of leptospirosis patients used insurance with an economic loss of USD 289.64 and a productivity loss value of USD 388,499. Patients infected with leptospirosis vary in age. Leptospirosis results in loss of patient productivity during treatment. Increasing prevention and control to prevent deaths and economic burdens on society and local governments is proposed to local governments.